Evaluating the efficiency of a living wall facade as a sustainable energy-saving alternative in hot arid regions - Ayah Mohamed Ramadhan; Ayman Hassaan Mahmoud (Journal of Engineering and Applied Science, 2023)
Abstract Buildings can generate heat from a variety of sources, including building occupants, the sun, lighting and radiance, and cooling equipment, the energy consumed by which results in heat. Egypt is experiencing rapid economic growth, improvements in urban spaces, and a reduction in green space, all of which contribute to the occurrence of environmental problems such as pollutants, increased CO2 emissions, and increased energy consumption. Furthermore, the study focuses on the cases of architectural buildings that have been combined with living green facade as an innovative facade in order to address the energy crisis and climate change. The study on live greening techniques on building facades has raised a lot of interest. The primary purpose of this research is to utilize simulation software to manage the energy consumption usage of a green facade and compare energy demand levels to the basic scenario. Living green façades can offer zone-sensitive cooling on building facades, which is especially important during summer sessions in hot areas. Green facade cooling loads have an effect on interior air quality by keeping the façade from warming up. The research investigates the cooling impact of three types of living green walls in Egypt using Design-Builder simulation software. To estimate the energy consumption rates of the base case building, the Design-Builder simulation program was used in conjunction with the Energy Plus engine. According to the findings, the indirect green façade with planter boxes of green walls has reduced the high energy consumption compared to the buildings with direct and indirect green façade, increased thermal comfort, and reduced CO2 emissions. As a result of the estimation, it was determined that the energy demand standards of the living wall were lower than the energy demand standards of buildings without the living wall of the same measurement, saving 75% of the energy.